1944
DOI: 10.5254/1.3546687
|View full text |Cite
|
Sign up to set email alerts
|

The Compounding of Hard GR-S

Abstract: A survey has been made of hard GR-S with regard to sulfur requirement and effects of various pigments, softeners, and accelerators on tensile strength, ultimate elongation, hardness, and stiffness. Of particular interest where the observations that hard GR-S had a higher tensile strength than hard Hevea rubber, and that hard GR-S did not undergo much loss in tensile strength when compounded with 60 volumes of channel black or semi-reinforcing black.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1949
1949
1949
1949

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Plasticizers known to be efficient in lowering the brittle point of other elastomers and resins were used in most instances. II) were obtained from the manufacturer and literature (4,19) or determined experimentally.…”
Section: Methodsmentioning
confidence: 99%
“…Plasticizers known to be efficient in lowering the brittle point of other elastomers and resins were used in most instances. II) were obtained from the manufacturer and literature (4,19) or determined experimentally.…”
Section: Methodsmentioning
confidence: 99%
“…GR-S compounding studies made by Morris, Mitt.on, Seegman, and Werkenthin (16) indicated that 50 parts of sulfur gave optimum physical results, and that by the proper choice of pigments, softeners, and accelerators, the time of cure could be shortened and ease of processing could be improved. It appeared difficult, however, to improve the physical properties beyond that of the base stock containing only GR-S and sulfur.…”
mentioning
confidence: 99%